Implementasi Model Pembelajaran Flipped Classroom Berbantuan Video Pembelajaran terhadap Kemampuan Pemahaman Konsep Matematis - Nursabilla, Febyliany; Yusepa Ginanjar Putra, Beni; Saputra, Jusep (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2023)
ABSTRACTMathematics lessons are subjects that relate to many concepts and the ability to understand mathematical concepts is the key in learning mathematics so that the ability to understand mathematical concepts is very important for students. However, students' ability to understand mathematical concepts is still low. The purpose of this study was to determine the effect of the flipped classroom learning model assisted by learning videos on the ability to understand mathematical concepts better than the flipped classroom learning model without the help of learning videos. This research method is quasi-experimental. The research design used was a pretest-posttest control group. The subjects in this study were selected randomly by using a purposive sampling technique where class VIII-A as the control class used the flipped classroom learning model without the help of learning videos and class VIII-C as the experimental class by getting the treatment of the flipped classroom learning model assisted by video learning with The instrument used to test the ability to understand mathematical concepts in the form of description questions. Data analysis was performed using a t-test or independent sample t-test with the help of SPSS 17.0 for Windows. The results showed that the ability to understand mathematical concepts of students with the flipped classroom learning model assisted by learning videos was better than the ability to understand mathematical concepts of students using the flipped classroom learning model without the help of learning videos or it could be concluded that there was an effect of the flipeed classroom learning model assisted by learning videos. Keywords: Ability to understand mathematical concepts, and flipeed classroom learning model assisted by learning videos.